2020
DOI: 10.7717/peerj.9526
|View full text |Cite
|
Sign up to set email alerts
|

Identifying agricultural pesticides that may pose a risk for birds

Abstract: In this study, we analyze changing patterns of pesticide use in agriculture in Great Britain over the 1990–2016 period, with respect to the risk they pose to birds. The weight of pesticides applied decreased by 51% between 1990 and 2016, but the area treated increased by 63% over the same period. Over this period, there has been considerable turnover in the pesticides used. The European Union (including Great Britain until 2020) has restricted or banned many pesticides for agricultural use, including organopho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 40 publications
0
16
1
Order By: Relevance
“…Finding sources of pesticide residues is a complex undertaking because many factors influence if and when a pesticide comes into contact with birds (Tassin de Montaigu & Goulson, 2020). Gross et al (2020) analyzed fecal samples in the 24‐h period following dosing and found residues of the parent active substance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finding sources of pesticide residues is a complex undertaking because many factors influence if and when a pesticide comes into contact with birds (Tassin de Montaigu & Goulson, 2020). Gross et al (2020) analyzed fecal samples in the 24‐h period following dosing and found residues of the parent active substance.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few decades, research has found a range of lethal and sublethal effects on birds caused by pesticides (Tassin de Montaigu & Goulson, 2020). Reduced survival and fertility, poisoning, abnormalities, and reduced mobility and navigation ability were found (Tassin de Montaigu & Goulson, 2020). We found no significant differences in relative weight, fat, or muscle score between exposed and unexposed Eurasian skylarks, but we did observe a possible decrease in the probability of a sample containing pesticide residues in individuals with better body condition (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…While there has been much research on the effects of insecticides on birds, other pesticides have received little or no attention. Fungicides and herbicides tend to be less acutely toxic to non-target species than insecticides, but are applied in higher quantities than insecticides (Lopez-Antia et al 2016;Tassin de Montaigu and Goulson 2020). A handful of studies have investigated the effects of seed treatment with fungicides on bird species (McGary et al 2001;Grote et al 2008;Satre et al 2009;Köhler and Triebskorn 2013;Lopez-Antia et al 2013Pandey and Mohanty 2015;Gross et al 2020;Ortiz-Santaliestra et al 2020;Mateo et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, we estimated the LD50 (mg/bird) (the dose of substance that gives a 50% probability of death), for each species observed feeding on treated seeds using scaling factors based on weight (Mineau et al 1996(Mineau et al , 2001Tassin de Montaigu and Goulson 2020). For the five insecticides and 15 fungicides that are frequently used as seed treatment (in Europe, North America, and/or Asia), the LD50 (mg/kg of body weight) was obtained from the Pesticides Properties DataBase (PPDB University of Hertfordshire).…”
Section: Estimation Of the Percentage Of Ld50 Ingestedmentioning
confidence: 99%
See 1 more Smart Citation